PENGEMBANGAN KONFLIK TOKOH PEREMPUAN DENGAN STRATEGI PEMERTAHANAN DIRI DALAM PROSA FIKSI INDONESIA - Yuni Pratiwi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe female characters’ self-defense against conflicts. It was carried out using the qualitative approach. The general finding shows that women use the self-defense against conflicts to avoid social and psychological disharmony. Female characters in Indonesian fictional prose serve as authors’ means of expressing ideas. To develop characters’ characterization, authors make female characters face a variety ofconflicts in life. They use techniques to develop characters with capabilities of defending the self against conflicts through an attempt reflecting an attitudinal wisdom in problem solving. The characters’ capabilities are attributable to life experience, education, tradition, life principles, and religions they believe in.